2021
DOI: 10.1007/s40670-021-01436-2
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Opinions of Anatomy Teaching Resources and Their Role in Achieving Learning Outcomes

Abstract: Several teaching resources are used to enhance the learning of anatomy. The purpose of this study was to examine the preference of medical students on the use of various resources to learn anatomy and their link to 12 learning outcomes. A selected response item questionnaire was administered that asked students to rank six laboratory teaching resources from most to least preferred, and rate how useful these six resources were towards achieving 12 learning outcomes. These learning outcomes covered many of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…Typically, participants would require multiple sources in the acquisition of their knowledge. This finding is supported by Abdullah et al, 13 who found that medical students used six resources (wholebody donor dissection, dissection videos, plastinated specimens, plastic models, printed resources and electronic resources) in their anatomy studies. In the current study, fewer resources (text resources, online videos and Primal Pictures) were used by participants.…”
Section: Themementioning
confidence: 55%
See 3 more Smart Citations
“…Typically, participants would require multiple sources in the acquisition of their knowledge. This finding is supported by Abdullah et al, 13 who found that medical students used six resources (wholebody donor dissection, dissection videos, plastinated specimens, plastic models, printed resources and electronic resources) in their anatomy studies. In the current study, fewer resources (text resources, online videos and Primal Pictures) were used by participants.…”
Section: Themementioning
confidence: 55%
“…Whole‐body donor dissection is consistently reported by students as one of the most effective ways to learn anatomy 13 . However, in an editorial, Lachman and Pawlina 30 point out that there is no empirical evidence to prove that whole‐body donor dissection leads to better academic outcomes in early undergraduate training; rather, continuous and effective engagement with the subject matter leads to better academic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 pandemic brought unprecedented challenges in medical education, including the University of the Philippines College of Medicine, disrupting traditional gross anatomy laboratory dissection methods and necessitating alternative learning modalities. 2 An international cohort of medical students claimed that the epidemic had a considerable unfavorable overall effect on their undergraduate education. 3 The role of non-cadaveric teaching methods in gross anatomy is still unclear.…”
Section: Introductionmentioning
confidence: 99%